Quality Education through Pesantren, Madrasahs, and Islamic Schools in Globalization Dynamics: Pendidikan Berkualitas Melalui Pesantren, Madrasah, dan Sekolah Islam dalam Dinamika Globalisasi - Zahra, Widya Aulia (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Globalization has reshaped educational landscapes worldwide, demanding institutions to remain adaptive, innovative, and competitive. Specific Background: In Indonesia, Islamic educational institutions—pesantren, madrasahs, and Islamic schools—play a strategic role in shaping human resources that are academically capable and spiritually grounded. Knowledge Gap: Despite their historical significance, these institutions often face stigma as traditional and less responsive to modern challenges, while limited studies systematically examine their integrative role in the globalization era. Aims: This study explores how pesantren, madrasahs, and Islamic schools adapt to global dynamics while preserving Islamic identity, and how their synergy contributes to improving national education quality. Results: Using qualitative analysis, the study finds that pesantren integrate local and global values through ecological curricula, madrasahs balance religious and general education while innovating in vocational and scientific fields, and Islamic schools with boarding models harmonize academic, spiritual, and social learning. Novelty: This research highlights the complementary roles of the three institutions, offering a holistic model of Islamic education that transcends the dichotomy between tradition and modernity. Implications: Strengthening collaboration among pesantren, madrasahs, and Islamic schools will foster inclusive, adaptive, and globally competitive education while safeguarding Indonesia’s cultural and spiritual identity.HIghlight : Pesantren integrate local and global values to strengthen student character. Madrasah enrich the national curriculum with Islamic perspectives. Islamic schools balance religious education and general knowledge in globalization Keywords : Globalization, Islamic Boarding Schools, Islamic Education, Islamic Schools, Education Quality